Palm Oil in the Millennial Era: The Effects of Digital Campaigns and Public Education on Brand Engagement through Awareness Generation Mediation in West Sumatra - Judijanto, Loso; Nugroho, Budi (Westscience Press, 2025)
This study investigates the impact of digital campaigns and public education on brand engagement through the mediating role of brand awareness in the palm oil industry of West Sumatra, Indonesia. The research was conducted in response to the growing need for sustainable branding and public perception management within an industry often associated with environmental controversy. A quantitative approach was employed using Structural Equation Modeling (SEM) with Partial Least Squares (SmartPLS 3.0). Data were collected from 115 respondents, primarily millennials, using a five-point Likert scale questionnaire. The results indicate that both digital campaigns and public education have significant positive effects on brand awareness and brand engagement. Moreover, brand awareness plays a partial mediating role, amplifying the indirect influence of digital campaigns and educational initiatives on engagement. The findings confirm the applicability of the Stimulus–Organism–Response (S-O-R) model, illustrating that digital and educational stimuli (S) enhance awareness (O), which subsequently drives engagement (R). The study contributes theoretically by integrating digital marketing communication and sustainability education into the brand engagement framework, and practically by offering strategies for improving consumer trust and advocacy through transparent, educational digital content.